Using OERs to improve teacher quality: emerging findings from TESSA - Wolfenden, Freda; Umar, Abdurrahman; Aguti, Jessica; Abdel Gafar, Amani (Commonwealth Forum on Open Learning, 2010)
The last decade has seen tremendous progress in primary pupil enrolment across much of sub-Saharan Africa but unfortunately in many areas this has not been accompanied by an improvement in pupil achievement. Attention and priorities are now expanding to embrace close scrutiny of the processes of classroom teaching and learning. Governments and donor agencies across the region are engaged in promoting a pedagogical paradigm shift to improve pupil attainment; a learner-centred classroom approach with pupil-teacher construction of knowledge through active inquiry. But to date systematic adoption and embedding of these progressive teaching methods has been limited and pupil learning achievements continue to be low. Much recent research on African classrooms shows that the dominant mode of teaching remains a teacher-led transmission style in which pupil talk is restricted to short, often chorus, answers to closed questions. ( Pontefract and Hardiman, 2005; Akyeampong et al, 2006; Altinyelken,2010; Henevald et al, 2006; Mtika & Gates, 2009) Recent UNESCO EFA reports draw attention to the importance of teacher quality for improving pupil achievement in schools and the key role of teacher education in shifting modes of interaction in African schools to those which more fully support pupils’ cognitive and linguistic learning (UNESCO, 2010). Teachers are potentially key agents of change. However such a focus on teachers is not unproblematic.